Association between complete blood count-derived inflammatory markers and the risk of frailty and mortality in middle-aged and older adults - Tang, Yu; Zhai, Ying; Song, Wenjing; Zhu, Tengxiao; Xu, Zichen; Jiang, Luqing; Li, Lei; Liu, Daoqin; Wu, Qiwen (Frontiers in Public Health, 2024)
Objective: This study aimed to evaluate the association between six complete blood count (CBC)derived inflammatory markers (neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), systemic immune-inflammatory index (SII), systemic inflammatory response index (SIRI), and pan-immune inflammation value (PIV)) and the risk of frailty and mortality. Methods: Data were obtained from the National Health and Nutrition Examination Survey (NHANES) 1999-2018. Mortality was identified using the National Death Index until December 31, 2019. Multiple logistic regression analysis was conducted to evaluate the association between six CBC-derived inflammatory markers and frailty. The Cox regression model assessed the association between six CBC-derived inflammatory markers and mortality in frail populations. Restricted cubic spline (RCS) was used to visualize the association of the six CBC-derived inflammatory markers with mortality risk. The predictive value of CBC-derived inflammatory markers for mortality was further assessed using a random survival forest (RSF) approach.Results: This study analyzed data from a total of 16,705 middle-aged and older participants. Among them, 6,503 participants were frail, with a mortality rate of 38.9341.47%. Multiple logistic regression analysis showed that NLR, MLR, PLR, SII, SIRI, and PIV were positively associated with frailty risk. The Cox regression model revealed that participants in the highest quartile had a significantly increased risk of death compared to those in the lowest quartile: